Políticas públicas de educação, proteção e defesa civil no Paraná: programa brigada escolar – defesa civil na escola - Leonardi, Maria Eugenia (2018)
This research had as motivation the interest in studying the Civil Defense Program in the School, its objectives and goals, relating it to people vulnerable to risks and disasters. The implementation of public social policies for education, protection and civil defense is a necessity, as well as the adequate application of the financial resources made available by the various government programs developed by civil protection and defense. The relevant aspect of the study is its immediate application, with a guiding proposal that the programs developed by the Government of the State of Paraná in education, protection and civil defense will enable social effectiveness among vulnerable communities and / or affected by disasters. The objective of this study was to study the School Brigade Government Program - Civil Defense at School, relating it to a Public Policy and Education in Civil Protection and Defense, examining its social effectiveness with the school system in the State of Paraná. At the end, a total of 3.15% of the teachers and pedagogues who work in educational establishments with administrative dependence of the State and belonging to the 4th Regional Coordination of Protection and Civil Defense were investigated, it was evidenced that the program is meeting its objectives , with the most secure schools, with better trained teachers and employees, who are better able to have a better understanding of the risks of fire and panic, to which all are subject, able to withdraw students safely in the event of accidents, insurance to act in emergencies not only in the school environment but also in the society in which they live. It was also pointed out that if these programs were treated in a responsible manner by our government, they would help build a just society that would provide dignity, working conditions and housing, so that education, protection and civil defense would arrive to all communities affected by disasters or at risk, which would make social effectiveness possible. In order to do so, it is concluded that the aforementioned program should be treated as a policy of education and its effectiveness within educational institutions and in society, as a State policy in Education.